Laparoscopic-Assisted Hysteroscopic Surgery for Endometrial Tumors Arising after Pelvic Radiation Therapy - Yuji Tanaka; Kimiko Hirata; Mariko Takahashi; Masashi Kobayashi (Hindawi Limited, 2020)
Uterine tumors detected after pelvic radiation therapy are rare. We report a case in which an endometrial tumor developed after pelvic radiation therapy for cervical cancer. The patient was a 70-year-old female with a history of pelvic radiotherapy for locally advanced cervical cancer. After 12 months of radiation therapy, magnetic resonance imaging showed tumors in the uterine cavity, and positron emission tomography-computed tomography showed no tumors, except uterine tumors. Since radiation therapy-induced cervical stenosis was conducted, endometrial examination could not be performed without anesthesia. As these tumors were detected after radiation therapy for uterine cancer, malignancy was considered. A laparoscopic-assisted transcervical hysteroscopic resection was performed for the diagnosis and treatment of uterine tumors after radiation therapy. This operative method was useful and enabled us to perform complete resection, observe the abdominal cavity, prepare for the possibility of secondary hysterectomy, and improve safety.